Impact of olfactory training on enhancing olfaction sense among patients with COVID-19 related olfactory dysfunction: A randomized controlled trial - Mohammad Hossein Akbarpour; Mitra Zandi; Ladan Sedighi; Mojtaba Ghanbari Ghalesar (Golestan University of Medical Sciences, 2024)
Background: Olfactory dysfunction, a prominent complication of COVID-19, significantly impacts patients' quality of life, persisting for months after infection. Exploring diverse methodologies to address this issue necessitates scholarly investigation. Therefore, our primary objective was to assess the impact of olfactory training on enhancing olfaction sense among COVID-19 patients. Methods: This randomized controlled trial employed a pretest-posttest design to assess COVID-19 patients experiencing olfactory dysfunction at the Babol Health Center in northern Iran. Patients were allocated to either the control or intervention group using closed envelopes. Both groups, consisting of 50 patients each, completed the Olfactory Disorders - Negative Statements (QOD-NS) questionnaire before the intervention. Over a six-week period, participants in the intervention group were exposed to Phenylethyl alcohol, Eucalyptus, Citronol, and Eugenol twice daily, rotating each scent for 20 seconds with ten-second breaks in between, while the control group received no intervention. Independent and paired t-tests were utilized to analyze the relationship between the groups before and after the intervention, with analysis conducted using SPSS 16. The significance level was set at less than 0.05. Results: The mean score of olfactory disorder among patients before the intervention in both the intervention and control groups was 24.32 ± 6.60 and 22.85 ± 8.04, respectively, showing no significant difference (P = 0.33). However, following the intervention, the scores decreased to 19.60 ± 5.74 and 22.52 ± 7.39 in the intervention and control groups, respectively, with a statistically significant difference observed (P = 0.034). Conclusion: Olfactory training demonstrated effectiveness in enhancing olfaction sense among patients with COVID-19 experiencing olfactory disorders. Consequently, it is recommended that nurses be trained to administer this program to COVID-19 patients with olfactory disorders upon discharge, facilitating their recovery process.